Comment on “a new approach to solve the Schrödinger equation with an anharmonic sextic potential” - Fernández, Francisco Marcelo (2022)
We analyze a recent application of the Nikiforov-Uvarov (NU) method to an N -dimensional anharmonic oscillator with a central-field sextic potential-energy function. We show that most of the equations derived by the author exhibit errors (or typos) and that his interpretation of the results may not be correct. By means of the Frobenius (power-series) method we derive exact particular solutions to the Schrödinger equation and compare them with those coming from the NU method.